Astragalus polysaccharide modulates the gut microbiota and metabolites of patients with major depressive disorder in an in vitro fermentation model: a pilot study - Mi, Yuwei; Lin, Chen; Zheng, Huowang; Wu, Ying; Hou, Yanbin; Hu, Jieqiong; Mao, Jiaxin; Dai, Ni; Li, Xiaoqiong; Lou, Zhongze; Ji, Yunxin (Frontiers in Nutrition, 2025)
Previous studies have found that Astragalus Polysaccharide (APS) and Lactobacillus plantarum PS128 (PS128) have potential antidepressant effects, but their effects on the gut microbiota and metabolites of major depressive disorder (MDD) are still unclear. We examined the effect of APS on gut microbiota and metabolites of first-episode and drug naïve MDD patients using in vitro fermentation, and further explored whether PS128 could enhance the utilization ability of APS. Fresh fecal samples from 15 MDD patients were collected, and analyzed for differences in gas production, gut microbiota, and tryptophan (Trp) related metabolites after 48 h of fermentation. APS fermentation increased the abundance of Bifidobacterium and decreased the abundance of Lachnoclostridium (p < 0.05). APS also increased total gas production and levels of indole lactic acid (ILA), Trp, and 5-hydroxytryptophan (5-HTP) (p < 0.05). Compared with APS, APS with PS128 synbiotics fermentation increased the abundance of Lactobacillus (p < 0.05), reduced total gas production and percentages of CO2, H2, and H2S (p < 0.05), and to some extent increased the levels of ILA, Trp, and 5-HTP, although not statistically significant (p > 0.05). Correlation analysis showed Bifidobacterium was positively correlated with ILA, Trp and 5-HTP; On the contrary, Lachnoclostridium was negatively correlated with ILA, Trp, and 5-HTP. All these results suggest that APS could regulate gut microbiota structure and Trp related metabolites in MDD patients; Compared to APS, APS and PS128 synbiotic fermentation could reduce gas production but shows limited ability to modulate gut microbiota structure or Trp related metabolites in MDD patients.